Transformasi Belajar dan Pembelajaran menuju Abad 21 - Sutiah, Sutiah (UIN Maulana Malik Ibrahim Malang, 2003)
The development of learning and learning patterns is directed to the four pillars as a whole, learning to know, learn to do, learn to be true, and learn to live together. These four pillars in the 21st century should be developed in an integrative way to be able to issue a refused out put. Learning and learning transformation in an effort to improve the quality and quality of education should continue to be pursued as a consequence of the demands of learning in accordance with the development of science and technology, learning styles, the development of learning and learning theories, and the needs and trends that occur in society as part of the development of the times. The transformation of learning and learning is intended to provide a passive atmosphere, character and learning patterns, depending on a single source, minimal and simplified facilities, uniform learning styles and not empowering learners. Furthermore, it should be developed into patterns and attitudes of learning that develop the integrity of learners actively, productively, and proactively. Pengembangan pola belajar dan pembelajaran diarahkan pada empat pilar secara utuh yaitu, belajar untuk mengetahui, belajar untuk berbuat, belajar untuk menjadi jati diri, dan belajar untuk hidup bersama. Keempat pilar ini pada abad 21 harus dikembangkan secara integratif agar mampu mengeluarkan out put yang refresentatif. Tranformasi belajar dan pembelajaran dalam upaya meningkatkan kualitas dan mutu pendidikan harus terus diupayakan sebagai konsekuensi dari tuntutan belajar yang sesuai dengan perkembangan ilmu pengetahuan dan teknologi, gaya belajar, perkembangan teori belajar dan pembelajaran, serta kebutuhan dan kecenderungan yang terjadi di masyarakat sebagai bagian perkembangan zaman. Transformasi belajar dan pembelajaran dimaksudkan untuk memberikan suasana, watak, dan pola-pola belajar yang pasif, tergantung dari satu sumber, fasilitas yang minim dan seadanya, gaya belajar yang seragam serta tidak memberdayakan peserta didik. Selanjutnya perlu dikembangkan menjadi pola dan sikap belajar yang mengembangkan keutuhan peserta didik secara aktif, produktif, dan proaktif.